2001
DOI: 10.1523/jneurosci.21-08-02820.2001
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Limbic Information Outflow by the Subthalamic Nucleus: Excitatory Amino Acid Projections to the Ventral Pallidum

Abstract: The subthalamic nucleus (STN), a component of the basal ganglia motor system, sends an excitatory amino acid (EAA)-containing projection to the ventral pallidum (VP), a major limbic system output region. The VP contains both NMDA and AMPA subtypes of EAA receptors. To characterize the physiology of the subthalamic pathway to the VP, and to determine the influence of EAA receptor subtypes, in vivo intracellular recordings, and in vivo extracellular recordings combined with microiontophoresis, were made from VP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 37 publications
5
54
0
Order By: Relevance
“…Thus, for the pooled data, 85% of the recorded action potentials were biphasic, the initial deflection for the action potential was in the negative direction for 73% and the average action potential peak to peak amplitude was 426 ± 24 μV, with a duration of 1.30 ± 0.03 ms. These action potential characteristics are consistent with prior studies (Mitrovic and Napier, 1996;Turner et al, 2001Turner et al, ,2002 and they suggest that we have been sampling from similar populations of VP neurons. Also similar to prior studies, the spontaneous firing rate for VP neurons recorded from saline-pretreated rats was 15 ± 1 spikes/s.…”
Section: Electrophysiologysupporting
confidence: 91%
“…Thus, for the pooled data, 85% of the recorded action potentials were biphasic, the initial deflection for the action potential was in the negative direction for 73% and the average action potential peak to peak amplitude was 426 ± 24 μV, with a duration of 1.30 ± 0.03 ms. These action potential characteristics are consistent with prior studies (Mitrovic and Napier, 1996;Turner et al, 2001Turner et al, ,2002 and they suggest that we have been sampling from similar populations of VP neurons. Also similar to prior studies, the spontaneous firing rate for VP neurons recorded from saline-pretreated rats was 15 ± 1 spikes/s.…”
Section: Electrophysiologysupporting
confidence: 91%
“…The limbic areas of the prefrontal cortex activate the STN, either by a direct excitatory input (the so-called 'hyperdirect pathway') or by an indirect disinhibitory pathway linking the NAC core and the STN via the VP (Maurice et al, 1998a, b). In return, the VP receives glutamatergic projections from the STN (Groenewegen and Berendse, 1990), thus allowing the STN to regulate the limbic output of the basal ganglia (Turner et al, 2001). Electrophysiological data have demonstrated that various neuronal populations in the NAC and the ventral striatum are activated by natural reward and drugs of abuse in behaving rats and monkeys (Bowman et al, 1996;Carelli, 2002;Carelli et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Within the cortico-basal ganglia-thalamocortical limbic loop, the subthalamic nucleus (STN) is a key structure that may modulate the basal ganglia outflow (Turner et al, 2001). The STN is, above all, currently known as a therapeutic target for Parkinson's disease treatment with high-frequency stimulation (HFS) (Limousin et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It demonstrated that a large part of the area referred to as 'substantia innominata' is actually an extension of the reward-related striatopallidal complex (Alheid and Heimer, 1988). In addition to receiving VS input, the VP also receives a glutamatergic input from the subthalamic nucleus (STN) and a dopaminergic input from the midbrain (Klitenick et al, 1992;Turner et al, 2001) (Figure 8).…”
Section: Ventral Pallidum (Figure 8)mentioning
confidence: 99%